2001
DOI: 10.1002/rcm.563
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of oligosaccharides by atmospheric pressure matrix‐assisted laser desorption/ionisation quadrupole ion trap mass spectrometry

Abstract: An ion source incorporating a fibre optic interface has been constructed for atmospheric pressure matrix-assisted laser desorption/ionisation quadrupole ion trap mass spectrometry. The configuration has been applied to the study of linear and complex oligosaccharides. Multi-stage tandem mass spectrometry (MSn, n = 2-4) experiments carried out in the ion trap enable extended fragmentation pathways to be investigated that yield structural information. Collisional activation of sodiated oligosaccharides, as demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 47 publications
3
39
0
Order By: Relevance
“…Work from Costello's group suggests that 6-azo-2-thiothymine (ATT, 1/45) is a better matrix under these conditions. Spectra from the article by Creaser, Reynolds, and Harvey (2002) showed more in-source fragmentation, particularly losses of water, than those recorded in vacuo but fragmentation within the ion trap was similar to that seen following ionization by other methods. Pressure at an estimated 1-10 mbar in a pulsed MALDI ion source attached to a Fourier-transform (FT) mass spectrometer has been reported to prevent both fragmentation of peptides and loss of sialic acid (Neu5Ac, 1/11) from the ganglioside GT1b (a-Neu5Ac-(2 !…”
Section: Instrumentationsupporting
confidence: 56%
See 1 more Smart Citation
“…Work from Costello's group suggests that 6-azo-2-thiothymine (ATT, 1/45) is a better matrix under these conditions. Spectra from the article by Creaser, Reynolds, and Harvey (2002) showed more in-source fragmentation, particularly losses of water, than those recorded in vacuo but fragmentation within the ion trap was similar to that seen following ionization by other methods. Pressure at an estimated 1-10 mbar in a pulsed MALDI ion source attached to a Fourier-transform (FT) mass spectrometer has been reported to prevent both fragmentation of peptides and loss of sialic acid (Neu5Ac, 1/11) from the ganglioside GT1b (a-Neu5Ac-(2 !…”
Section: Instrumentationsupporting
confidence: 56%
“…Collisional cooling of the ion beam is necessary to modulate the pulsed nature of the ion source. Creaser, Reynolds, and Harvey (2002) have interfaced an atmospheric pressure ion source to a Finnigan ion trap mass spectrometer and found that, unlike vacuum MALDI, esculetin (1/73) ionized carbohydrates more efficiently than DHB. Work from Costello's group suggests that 6-azo-2-thiothymine (ATT, 1/45) is a better matrix under these conditions.…”
Section: Instrumentationmentioning
confidence: 99%
“…Atmospheric pressure/matrix assisted laser desorption ionization (AP/MALDI) MS has already proved to be a very valuable tool in a number of important applications, including the identification of proteins,26 the structural analysis of oligosaccharides,27 the characterization of enzymes immobilized on solid support,28 and the study of phosphopeptides,29 due to its ability to detect intact molecular masses up to several 1000 Da 30…”
Section: Introductionmentioning
confidence: 99%
“…This instrument was applied to the analysis of the neutral oligosaccharide, difucosyllacto-N-tetraose [274]. UV AP-MALDI coupled to an ion trap mass spectrometer was used by Creaser et al [275] to acquire MS n spectra of sodium adducts of neutral oligosaccharides and by Moyer et al for the negative mode analyses of sialylated oligosaccharides [276]. More recently, the analysis of sialylated oligosaccharides using infrared atmospheric pressure matrix assisted laser desorption/ionisation on an ion trap mass spectrometer (IR AP-MALDI-ITMS) has been reported [277,278].…”
Section: Fragmentation Of Glycansmentioning
confidence: 99%